Komunikasi interpersonal menyenangkan dalam pengurusan organisasi menurut perspektif Islam: Satu analisis di Kumpulan Jaminan perniagaan (KJP) Telekom Malaysia Berhad / Zulkifli Ariffin - Zulkifli, Ariffin (2017)
Communication satisfying may not be adequate to conceptualize as effective interpersonal communication in Malaysia workplace, of which most of the organization’s members are Muslim. Hence, there is a need to study the conceptual construct of pleasant and unpleasant interpersonal communication from the Islamic perspective. The concept of communication in Islam, besides establishing relationship between human beings, is to establish the vertical relationship with the Creator of human beings that is Allah SWT. Communication with Allah SWT is reflected through performance of religious obligations and worships such as prayer, fasting, zakat and pilgrimage to achieve piety status. Whereas the concept of communication from western perspective focuses on the human beings relationship through social interactions or “muamalah”, reflected in all aspects of human interactions like in social, culture, political, economy, and art; signifying the importance of this research alongside in identifying the communication skills, forms, types and interpersonal communications trends perceived as pleasant and unpleasant in the context of organizational management according to Islamic perspective. The importance of this research in organizational management from the Islamic perspective is to strengthen the understanding, motivation, and commitment of GBA (Group Business Assurance) staff in defining, planning, executing, and completing jobs successfully through management process naturally, effectively, and innovatively through and with other staff collaboratively in efforts to achieve the organization’s goals and objectives. At the same time, organizational resources are used and leveraged strategically in global business environment that is dynamic and constantly changing, in meeting and attaining organization objectives towards “al-falah” success in this world and in Hereafter. To do so, Social Exchange Theory by Homan (1961) underlie this study. with the value of Analyzed with Kruskall Wallis with SPSS and the value sig = 0.024 (<0.05), it shows item cooperation and friendliness have significant relationship with interpersonal communication to please at the same time also study and which related by Luthans (2005), Magnus (2009), and Hung & Lim (2013) had been used guidance. Meanwhile, Cronbach’s Alpha’s value of 0.67 is significant and accepted to form the instrument used that is the survey form. The study has a targeted population of 91 covering all staff in the Group Business Assurance (GBA) Department, at 11th Floor, North and South, Tower of Telekom Malaysia. Half of the targeted population or 45 staffs responded and this is the sample size. Key findings from the research showed existing staffs need interpersonal communication skill. Interpersonal communication spoken form and the type not formal found to be effective and giving satisfaction at the workplace. Interpersonal communication trend vertical is interpersonal communication that effective meanwhile interpersonal communications trend horizontal can give work satisfaction. However, the overall interpersonal communication in organizational management according to Islamic perspective perceived as pleasant by staffs in GBA.